The effect of chronic amphetamine treatment on cocaine-induced facilitation of intracranial self-stimulation in rats - Bauer, Clayton T. (2014)
RATIONALE: Chronic amphetamine treatment reduces cocaine self-administration in pre-clinical and clinical settings, and amphetamine has been proposed as a candidate medication for treatment of cocaine abuse. OBJECTIVES: Investigate whether chronic amphetamine treatment can decrease the abuse-related cocaine effects in an assay of intracranial self-stimulation (ICSS). METHODS: Thirteen adult male Sprague-Dawley rats were equipped with intracranial electrodes targeting the medial forebrain bundle and trained to lever press for pulses of brain stimulation in a “frequency-rate” ICSS procedure. Cocaine (10 mg/kg) was administered before (Day 0), during (Days 7 and 14) and after (post-treatment days 1 and 3) two weeks of continuous treatment with either amphetamine (0.32mg/kg/hr, n=7) or saline (n=6) via osmotic pump. RESULTS: Prior to treatment, cocaine facilitated ICSS in all rats. Saline treatment had no effect on baseline ICSS or cocaine-induced facilitation of ICSS at any time. Conversely, amphetamine produced a sustained though sub-maximal facilitation of baseline ICSS, and cocaine produced little additional facilitation of ICSS during amphetamine treatment. Termination of amphetamine treatment produced a depression of baseline ICSS and recovery of cocaine-induced facilitation of ICSS. CONCLUSIONS: These data suggest that chronic amphetamine treatment blunts expression of abuse-related cocaine effects on ICSS in rats.